2003
DOI: 10.1037/0022-0167.50.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Improving the effects of psychotherapy: The use of early identification of treatment and problem-solving strategies in routine practice.

Abstract: Client-focused research systems have been developed to monitor and provide feedback information about clients' progress in psychotherapy as a method of enhancing outcome for those who are predicted to be treatment failures. In the current study, the authors examined whether feedback regarding client progress and the use of clinical support tools (CSTs) affected client outcome and number of sessions attended. Results showed that clients in the feedback plus CST group stayed in therapy longer and had superior ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
320
3
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(342 citation statements)
references
References 45 publications
12
320
3
7
Order By: Relevance
“…In these studies therapists directly recruited the patients, which may have increased participation rates. However, other studies have used similar recruitment procedures to our study [9][10][11][12][13][14]. They have achieved higher participation rates than in our study possibly because the OQ-45 was a standard tool for all patients in those studies.…”
Section: Limitationscontrasting
confidence: 40%
See 1 more Smart Citation
“…In these studies therapists directly recruited the patients, which may have increased participation rates. However, other studies have used similar recruitment procedures to our study [9][10][11][12][13][14]. They have achieved higher participation rates than in our study possibly because the OQ-45 was a standard tool for all patients in those studies.…”
Section: Limitationscontrasting
confidence: 40%
“…A recent meta-and mega-analytic review [8] of data from six large studies [9][10][11][12][13][14] reported that different feedback procedures were effective in enhancing treatment outcome, especially for those patients at risk of treatment failure. A total of 6,151 subjects were included and, of these, 1,382 (22%) were at risk of treatment failure.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral interventions that promote problem solving tend to have stronger effects and are associated with greater engagement (Whipple et al, 2003). Finally, parents also seemed to be better at acknowledging their own responsibility in their child's development.…”
Section: Discussionmentioning
confidence: 99%
“…The HAq-II is a 19-item self-report scale; it can measure the alliance from either the patient or the therapist point of view. [31] showed that outcome of psychotherapy (as measured by the OQ-45) for patients who began treatment with a poor start improved when therapists collected data on the patient's perception of the alliance using the HAq-II.…”
Section: The Therapeutic Relationshipmentioning
confidence: 99%